Financial Management Practices on Financial Performance at Selected Private Insurance Companies, Kigali, Rwanda (International Journal of Scientific Research and Management (IJSRM), 2021)
The general objective of this dissertation was to assess the relationship between financial management practices and the financial performance of private insurance companies in Rwanda. It was guided by the following specific objectives which are to assess the impact of financial management practices on return on investment (ROI) of insurance companies in Rwanda; to examine the impact of financial management practices on return on assets (ROA) of insurance companies in Rwanda and to find out the impact of financial management practices on return on equity (ROE) of insurance companies in Rwanda. The research design used a descriptive causal approach to research that takes cross-sectional data into account and helped the researcher to use the questionnaire and documentary review the primary data collection tool and the secondary data collection analysis, respectively. For the first objective, the study shows that an adjusted R square of 44.8% of ROI of private insurance companies in Rwanda is attributed to a combination of the four factors independent factors (fixed assets management, accounting information system, financial reporting analysis, and capital structure management) used by private insurance companies in Rwanda. For the second objective, the findings revealed that an adjusted R square of 80.9% of return on assets of private insurance companies in Rwanda is attributed to a combination of the four factors independent factors (fixed assets management, accounting information system, financial reporting analysis, and capital structure management) used by private insurance companies in Rwanda .For the third objective, the findings revealed that an adjusted R square of 36.8% of return on equity (ROE) of private insurance companies in Rwanda is attributed to a combination of the four factors independent factors (fixed assets management, accounting information system, financial reporting analysis, and capital structure management) used by private insurance companies in Rwanda. The study concluded that working capital management, capital structure management, financial reporting analysis and accounting information system, play significant positive effect on financial performance of private insurance companies in Rwanda while fixed asset management have negative effect on the financial performance of private insurance companies in Rwanda. The study is recommending insurance companies’ management to implement recommended steps considered as possible ways to ensure improvement of their financial management practices for better financial performance. Key words: Financial management practices, financial performance, insurance companies, Rwanda